572 Extent of cardiac damage and mortality in patients undergoing transcatheter aortic valve implantation. (17th December 2020) - Avvedimento, Marisa; Leone, Attilio; Castiello, Domenico Simone; Angellotti, Domenico; Ilardi, Federica; Esposito, Roberta; Iapicca, Cristina; Piccolo, Raffaele; Cirillo, Plinio Lorenzo; Franzone, Anna; Esposito, Giovanni
Abstract: Aims: Degenerative aortic stenosis (AS) is the most common heart valve disease among people ≥65 years in developed countries, with an increasing prevalence due to population ageing. A recently proposed staging classification of AS is based on the assumption that there is a continuum in the pathophysiology of LV structural and functional changes induced by AS. Such system showed prognostic ability among patients from the PARTNER 2 trial as well as in asymptomatic subjects with moderate to severe AS, thus challenging the current management of the disease. The aim of our study was to assess the prognostic performance of this staging classification in a real-world cohort of patients undergoing transcatheter aortic valve implantation (TAVI) and to investigate the eventual impact of the procedure on the extent of extra-aortic valve cardiac damage. Methods and results: A staging classification was applied to 262 patients from the EffecTAVI Registry. The following criteria for staging classification of cardiac damage were applied at baseline (within 1 month before TAVI) and after the procedure (within 30-day): Stage 0, no extra-aortic valve cardiac damage; Stage 1, LV damage as defined by the presence of LV hypertrophy (LV mass index >95 g/m2 for women, >115 g/m2 for men), severe LV diastolic dysfunction (E/e' >14) or LV systolic dysfunction (LV ejection fraction, LVEF <50%); Stage 2, left atrial (LA) and/or mitral valve damage as defined by the presence of LA enlargement (LA volume > 34 ml/m 2 ) and/or moderate-severe mitral regurgitation and/or atrial fibrillation; Stage 3, pulmonary vasculature and/or tricuspid valve damage as defined by the presence of systolic pulmonary hypertension (systolic pulmonary arterial pressure, PAPS > 60 mmHg) and/or moderate/severe tricuspid valve regurgitation; Stage 4, right ventricular (RV) damage as defined by the presence of moderate-severe RV systolic dysfunction (tricuspid annular systolic excursion, TAPSE < 17 mm). The primary endpoint of the study was all-cause mortality at 1-year. Secondary endpoints included cerebrovascular accident, myocardial infarction, permanent pacemaker implantation, endocarditis and re-hospitalization for all causes. At baseline, 23 (8.7%) patients were in Stage 0/1 (no cardiac damage/left ventricular damage), 106 (40.4%) in Stage 2 (left atrial or mitral valve damage), 59 (22.5%) in Stage 3 (pulmonary vasculature or tricuspid valve damage) and 74 (28.3%) in Stage 4 (right ventricular damage). At 30-day after TAVI, a lower prevalence of advanced stages of cardiac damage than baseline, mainly driven by a significant improvement in left ventricular diastolic parameters and right ventricular function, was reported. At 1-year, a stepwise increase in mortality rates was observed according to staging at baseline: 4.3% in Stage 0/1, 6.6% in Stage 2, 18.6% in Stage 3 and 21.6% in Stage 4 (p = 0.08). No differences were found in secondary endpoints. Conclusion: TAVI has an early beneficial impact on the left ventricular diastolic and right ventricular function. However, the extent of cardiac damage at baseline significantly affects the risk of mortality at 1-year after the procedure.